Cultural Beliefs and Practices Influencing the Birthing Process: A Qualitative Study - Karki, Gyanendra Man Singh; KC, Heera; Pandey, Shuvechha (Annapurna Journal of Health Sciences, 2023)
Introduction: Cultural beliefs and practices of patients play an important role in healthcare service utilization. Women often exhibit their faith in culture during pregnancy and childbirth process, but little is understood about its impact from conception to post-delivery status. This study was carried out to explore cultural beliefs and practices during birthing process among women delivered at Birat Medical College Teaching Hospital. Methods: We conducted a phenomenological cross sectional qualitative study at the Department of Obstetrics and Gynecology, Birat Medical College Teaching Hospital from 25 July 2022 to 25 October 2022. Ethical clearance was obtained from the Institutional Review committee, Birat Medical College. In-depth interview was conducted among 20 postnatal women who had elective cesarean sections. Audiotaped in-depth interview was transcribed verbatim and analyzed by using the thematic framework method. Results: 13 out of overall participants stated that they had chosen the auspicious date, day and time of birth according to astrologer’s advice. Most were participants themselves who believe in astrology. Some participants stated that they had offered prayers and wishes in a holy temple to bear a child and also followed religious rituals in wish of a preferred sex of child. Other habits like restricting certain foods, worshiping gods were also found. Conclusion: Cultural beliefs and practices have a great impact on birthing process. Women believed in palm reading, astrology and followed their advice for estimating auspicious time of birth. Some other religious beliefs like faith in god, worshiping, offering prayers and food restriction habits were also seen.